Establishment and Characterization of NCC-MFS5-C1: A Novel Patient-Derived Cell Line of Myxofibrosarcoma - Ryuto Tsuchiya; Yuki Yoshimatsu; Rei Noguchi; Yooksil Sin; Takuya Ono; Taro Akiyama; Jun Sugaya; Eisuke Kobayashi; Naoki Kojima; Akihiko Yoshida; Seiji Ohtori; Akira Kawai; et al. (Cells, 2022)
Myxofibrosarcoma (MFS) is a highly aggressive malignancy with complex karyotypes and a postoperative recurrence tendency, owing to its strong invasiveness. Although systemic chemotherapy is considered in patients with unresectable MFS, the efficacy of conventional chemotherapy is hitherto unclear. Recently, drug screening analysis using a large number of tumor cell lines has been attempted to discover novel therapeutic candidate drugs for common cancers. However, the number of MFS cell lines is extremely small because of its low incidence—this hinders the conduction of screening studies and slows down the development of therapeutic drugs. To overcome this problem, we established a novel MFS cell line, NCC-MFS5-C1, which was shown to harbor typical MFS genetic abnormalities and thus had useful properties for in vitro studies. We conducted the largest integrated screening analysis of 210 drugs using NCC-MFS5-C1 cells along with four MFS cell lines, which we previously reported. Bortezomib (a proteasome inhibitor) and romidepsin (a histone deacetylase inhibitor) showed stronger antitumor effects than the standard drug, doxorubicin. Therefore, the NCC-MFS5-C1 cell line can potentially contribute to elucidating MFS pathogenesis and developing a novel MFS treatment.